Invitro Antimicrobial Activities of Mitracarpus scaber Against Some Common Bacteria of Aquatic Origin - Ajadi, Abdullateef Abiodun; Emikpe, Benjamin; Akeem, Ahmed (Media Kedokteran Hewan, 2021)
Some plants have been reported to be of medicinal values and reserve some antimicrobial properties. One of such plants is Mitracarpus scaber and its effect on bacterial growth is evaluated. The study aimed at evaluating the phytochemical analyses and antimicrobial potentials of Mitracarpus scaber against aquatic bacteria including Aeromonas, Bacillus, Vibrio and Staphylococcus Spp. Leaves of Mitracarpus scaber were collected, washed and air dried and phytochemical analysis and antimicrobial investigation of ethanolic and aqueous extracts of the leaves were carried out against a panel of bacteria isolated from diseased catfish from various farms. The phytoconstituents detected include saponins, tannins, flavonoids, tarpenoids, steroids, anthraquinones and alkaloids in both aqueous and ethanolic extracts. Both aqueous and ethanolic extracts of M. scaber showed varying degree of antibacterial activities but ethanolic extract showed a higher activity against the pathogens tested. The ethanolic extract had zones of inhibition similar to that of standard antibiotics (enrofloxacin) across all tested microbes.  The lowest minimum inhibitory concentration of ethanolic extract of M. scaber was against Bacillus sp with 10mg/ml while the highest was 85mg/ml against Staphylococcus species. The results of the assays showed promising evidences that M. scaber is a potential antibacterial agent against aquatic microbes.  However, further studies are recommended to fractionate its constituents and determine the in vitro and in vivo anti-microbial activities and the exact mechanism of action of the constituents.